Unsteady flow and heat transfer past an axisymmetric permeable shrinking sheet with radiation effect. - Md. Ali, Fadzilah; Nazar, Roslinda; Md. Arifin, Norihan; Pop, Ioan (Wiley Blackwell, 2011)
In this paper, the problem of unsteady axisymmetric boundary layer flow and heat transfer induced by a permeable shrinking sheet in the presence of radiation effect is studied. The transformed boundary layer equations are solved numerically by an implicit finite-difference scheme known as the Keller-box method. The influence of radiation, unsteadiness and mass suction parameters on the reduced skin friction coefficient f''(0) and the heat transfer coefficient -θ'(0), as well as the velocity and temperature profiles are presented and discussed in detail. It is found that dual solutions exist and suction parameter delays the separation of boundary layer.